Evaluation of location of cosmetic customization in public buildings in South-West Nigeria - Olatunde Folaranmi Adedayo; Ayomide Taiwo Ale; Nasir Muhammad Yahaya-Loko; Victor Samuel Adekunle (Journal of Engineering and Applied Science, 2024)
Abstract The categorization of public buildings is such that it covers all buildings that are accessible to the public; however, many public buildings that are either fully or partially privately owned usually undergo some form of cosmetic customization in an attempt to communicate the aspirations of the owners or occupants of the building or the space within the building to the users. This paper aims to examine the location and aspects of the buildings that are affected by cosmetic customization as they relate to the occupants and owners of the buildings. The study adopted mixed methods of qualitative and quantitative research approach, it used both a questionnaire and observation checklist to obtain data from the selected buildings and the respondents. Eleven public categories of public buildings were selected and 30 copies of the questionnaire were administered to each category. The data was analyzed using descriptive statistics from SPSS software and the results are presented in tables and charts. It was observed that a high percentage of the customization was undertaken within the building and the ceiling aspect of the interior was the most modified part of the building. The study concluded that cosmetic customization was undertaken in all of the public buildings examined, and this action helped project the image the owners wanted to put forward as their form of brand identity using the building.